AI and Machine Learning for on-Device Development a programmer's guide - Moroney, Laurence (O'Reilly Media, Incorporated, 2021)
Chapter 2. Introduction to Computer Vision -- Using Neurons for Vision -- Your First Classifier: Recognizing Clothing Items -- The Data: Fashion MNIST -- A Model Architecture to Parse Fashion MNIST -- Coding the Fashion MNIST Model -- Transfer Learning for Computer Vision -- Summary -- Chapter 3. Introduction to ML Kit -- Building a Face Detection App on Android -- Step 1: Create the App with Android Studio -- Step 2: Add and Configure ML Kit -- Step 3: Define the User Interface -- Step 4: Add the Images as Assets -- Step 5: Load the UI with a Default Picture.
Object Detection in iOS with ML Kit. - Online resource; title from digital title page (viewed on September 01, 2021)
Keywords: Machine learning; Apprentissage automatique